Sex, violence, and justice : contraception and the Catholic Church - Kalbian, Aline H., 1954- (Moral traditions series., 2014)
In 1968, Pope Paul VI published Humanae vitae, the encyclical that reaffirmed the Catholic Church's continued opposition to the use of any form of artificial contraception. In Sex, Violence, and Justice: Contraception and the Catholic Church, Aline Kalbian outlines the Church's position against artificial contraception as principally rooted in three biblical commandments. In addition, Kalbian shows how discourses about sexuality, both in the Church and in culture, are often tied to discourses of violence, harm and social injustice. These ties reveal that sexual ethics is never just about sex.